Effect of ternary blends of bio-ethanol, diesel and castor oil on performance, emission and combustion in a CI engine - Prakash, T.; Geo, V. Edwin; Martin, Leenus Jesu; Nagalingam, B. (Renewable energy, 2018)
Some properties of castor oil such as extremely high viscosity and high water content complicate the use of neat castor oil (NCO) as a fuel for compression ignition engines. The brake thermal efficiency, emission and combustion characteristics of a diesel engine operation compared with neat castor oil is far inferior. However, neat castor oil has an affinity for alcohol because of high Ricinoleic Acid about 89.5% and hence mixes in any proportion without any phase separation and also diesel easily blends with neat castor oil. The blending of bio-ethanol and diesel enhances the combustion of NCO. The present study aims to obtain an optimum ternary fuel blend with neat castor oil-diesel- bio-ethanol, which can be used in small diesel engines. Experimental investigation reveals that the ternary blend of neat castor oil-diesel-bio-ethanol fuel with the volume ratio of NCO40 + D30 + E30 is optimum. At full load, the thermal efficiency of the engine operating with NCO40 + D30 + E30 is 31.25%, which is closer to diesel operation of 32.94% and specific NO emission for NCO40 + D30 + E30 is 6.11 g/kWh, whereas it is 8.17 g/kWh for diesel. NCO40 + D30 + E30 has a smoke emission of 68% opacity, but the smoke level of the base diesel engine is 57% opacity. •This paper falls under the main area of alternate fuels for transportation engines.•Preparation of homogeneous ternary blends of neat castor oil, bio-ethanol and diesel.•Analyze the effect of Ricinoleic Acid on Ternary blends.•Given a detailed discussion of ternary blends as fuel in IC engines through performance, emission and combustion analysis.